Management of primary headache in emergency services of Santos and surrounding towns - Fragoso, Yara Dadalti; Fonseca, Priscilla Lopes da; Fortinguerra, Marcelo Bougartner; Cominato, Louise; Matte, Guilherme de Oliveira; Oliveira, Claudia Medeiros (São Paulo Medical Journal, 1998)
OBJECTIVES: Primary headaches are often seen by Clinicians on duty at Emergency Services. We have investigated the treatment of such patients by 43 medical doctors who have been working at Emergency Services in the city of Santos and surrounding towns for many years. RESULTS: We confirmed the high prevalence of primary headaches in Emergency Services. There seem to be diagnosis difficulties concerning differentiating attacks of migraine and tension type headache. We also observed that IV dipirone was the most frequently prescribed treatment for patients with primary headaches in this study. There is no protocol in the literature which recommends IV dipirone for the treatment of migraine attacks or other primary headaches. CONCLUSION: It would be advisable to perform controlled double blind studies in order to verify the advantages of IV dipirone in the treatment of intense attacks primary headaches. We concluded that headache management recycling programs could be of interest for doctors who regularly work at Emergency Services.